Biohybrid Nanomaterials in Biomedicine: Current Trends and Future Prospects - Asadi, Alireza; Mohammadi, Elaheh; Hosseinpour, Setareh (Advances in Applied NanoBio-Technologies, 2025)
The integration of biohybrid nanomaterials into dentistry represents a transformative approach to oral healthcare, offering tissue-mimetic solutions for oral health care. These advanced materials, including hydroxyapatite-based nanoparticles, bioactive glass, nanocellulose, peptide-based systems, and carbon-based nanomaterials, enable targeted therapies for enamel remineralization, dentin regeneration, antimicrobial action, and mechanical reinforcement of dental restorations. By leveraging their unique properties, such as biocompatibility, bioactivity, and stimuli-responsiveness, biohybrid nanomaterials address limitations of traditional dental materials, such as poor durability and lack of regenerative capabilities. This review highlights current applications in preventive and therapeutic dentistry, explores challenges related to scalability and safety, and discusses prospects for personalized and sustainable dental care.